Customization approach and software quality mapping model to improve SaaS customization - Ali, Abdulrazzaq Qasem (2020)
Software as a Service (SaaS) is widely used for a wide range of applications development. Therefore, the SaaS should capacitate itself to offer services to many customers having their own specific requirements, without encountering software quality problems. Hence, understanding SaaS customization’s impact on the software quality will mitigate the risk. However, studies on the effects of software customization on the quality of SaaS application are still lacking. Furthermore, it is essential to record the customization category to ascertain the impact and risks linked to specific types of customization. Any form of SaaS customization is likely to influence the software quality. Accordingly, customization types and customization practices in the context of multi-tenant SaaS should be identified prior to assessing the impact of customization. Although several researchers have clearly stated the need for emphasis on SaaS application customization, there remains a dearth of knowledge on software customization types and practices in the SaaS multi-tenant context. Hence, the aim of this research is to propose a customization approach and software quality mapping model that provides three main information: 1) software customization types and a list of common practices for each customization type in the SaaS Multi-Tenant context, 2) key quality attributes of SaaS applications associated with customization, and 3) empirical evidence on the impact of each customization type over SaaS quality. The proposed model was initially constructed from 46 customization practices and 13 quality attributes in the SaaS multi-tenant context. Each investigated customization practice was deductively assigned to one of the customization approaches (personalization, configuration, composition, modification, integration, and extension). The model was content validated in two rounds and necessary changes were made as suggested by the content experts. Subsequently, the internal consistency reliability study among 34 software engineers was conducted and showed that all constructs are reliable. The model then had undergone further investigation to empirically assess construct reliability, construct validity, and the effect of each customization approach on the SaaS quality by surveying 244 software professionals who have been involved in SaaS development life cycle. The collected data was then analyzed using factor analysis and Structural Equation Modeling (SEM). The model was modified based on the results of factor analysis. The test for reliability and validity revealed that the model is acceptable. The findings of the structural model assessment show that all customization approaches significantly influence the quality of SaaS application except integration. Furthermore, it revealed that the impact of configuration and composition approaches on SaaS quality is positive, while the impact of other approaches is negative. The results of model validation showed experts positive feedback on the usefulness of the model. As a conclusion, this research provides a wider view of the impact of software customization on SaaS quality from different aspects (e.g., customization types, quality attributes, and potential impacts). This is a useful guidelines and references for both SaaS researchers and SaaS practitioners.